Acidic oligosaccharide sugar chain combined with hyperbaric oxygen delays D-galactose-induced brain senescence in mice via attenuating oxidative stress and neuroinflammation. (December 2022) - Wang, Guimei; Wang, Xiaolin; Zheng, Xiaoyue; Sun, Shuqin; Zhao, Jing; Long, Ying; Mao, Yongjun
Abstract: Aging is fundamental to neurodegeneration and dementia. Preventing oxidative stress and neuroinflammation are potential methods of delaying the onset of aging-associated neurodegenerative diseases. The acidic oligosaccharide sugar chain (AOSC) and hyperbaric oxygen (HBO) can increase the expression of antioxidants and have a neuroprotective function. In this study, we investigate the ability of AOSC, HBO, and AOSC + HBO to prevent D -gal-induced brain senescence. The Morris water maze and Y-maze test results showed that all three therapies significantly attenuated D -gal-induced memory disorders. A potential mechanism of this action was decreasing elevated levels of oxidative stress and neuroinflammation. The western blot and morphological results showed that all three therapies decreased D -gal-induced neuroinflammation and downregulated inflammatory mediators including the nuclear factor κ-light-chain-enhancer of activated B cells, cyclooxygenase-2, interleukin-1β, and tumor necrosis factor alpha. Taken together, our results indicated that AOSC, HBO, and AOSC + HBO therapies attenuated D -gal-induced brain aging in mice by repressing RAGE/NF-KB-induced inflammation, the activation of astrocytes and microglia, and a decrease in neuronal degeneration. These could be useful therapies for treating age-related neurodegenerative diseases such as Alzheimer's disease. Furthermore, HBO combined with AOSC had a better effect than HBO or AOSC alone. Highlights: AOSC, HBO, and AOSC + HBO treatments alleviated D -gal–induced memory loss in mice. The neuroprotection was exerted by attenuating neuroinflammation. They could be beneficial therapies for aging-related diseases such as AD. HBO + AOSC therapy may produce more profound therapeutic effects.